Shock metamorphism of Elephant Moraine A79001: Implications for olivine-ringwoodite transformation and the complex thermal history of heavily shocked Martian meteorites - Walton, Erin L. (My University, 2013)
Lithology A of Martian meteorite Elephant Moraine (EET) A79001 contains fragments entrained within a 100 mu m-thick shear-induced shock vein. These fragments, the shock vein matrix and walls of olivine along the vein, as well as shock deformation and transformation in rock-forming minerals in the bulk rock, were investigated using scanning electron microscopy, the electron microprobe and Raman spectroscopy. The presence of ringwoodite, the spinel-structured high-pressure (Mg,Fe) (sub 2) SiO (sub 4) polymorph, has been confirmed in EETA79001 for the first time. Ringwoodite occurs within and around the shock vein, exhibiting granular and lamellar textures. In both textures ringwoodite consists of nearly equal 500 nm size distinct grains. Ringwoodite lamellae are 115 nm to 1.3 mu m wide. Planar fractures in olivine provided sites for heterogeneous nucleation of ringwoodite. Analyses performed on the largest grains (> or =1 mu m) show that ringwoodite is consistently higher in iron (Fa (sub 27.4-32.4) ) relative to surrounding olivine (Fa (sub 25.1-267.7) ), implying that there was Fe-Mg exchange during their transformation, and therefore their growth was diffusion-controlled. In the shock environment, diffusion takes place dynamically, i.e., with concurrent deformation and grain size reduction. This results in enhanced diffusion rates (> or =10 (super -8) m (super 2) /s) over nm - mu m distances. Shock deformation in host rock minerals including strong mosaicism, pervasive fracturing, polysynthetic twinning (pyroxene only), extensive shock melting, local transformation of olivine to ringwoodite, and complete transformation of plagioclase to maskelynite in the bulk rock, indicate that EETA79001 was strongly shocked. The short shock duration (0.01 s) combined with a complex thermal history, resulted in crystallization of the 100 mu m thick shock vein in EETA79001 during the pressure release, and partial back-transformation of ringwoodite to olivine. Based on the pressure stabilities of clinopyroxene+ringwoodite, crystallization at the shock vein margin began at nearly equal 18 GPa. Olivine and clinopyroxene crystallized at <14 GPa closer to the shock vein center. These represent a minimum limit to the shock pressure loading experienced by EETA79001.
Keywords: achondrites; Antarctica; chemical composition; cosmochemistry